Serum melatonin level in patients with rheumatoid arthritis: A systematic review and meta-analysis - Fahimeh Mohammadghasemi; Masoumeh Faghani; Zahra Rafat; Elahe Sasani (Indian Journal of Rheumatology)
Objective: Melatonin is the major secretory product of the pineal gland and may play a role in the etiology and clinical symptoms of rheumatoid arthritis (RA). This systematic review and meta-analysis were conducted to determine the morning serum melatonin level in patients with RA compared to non-RA patients. Materials and Methods: We searched English databases (PubMed, Web of Science, Scopus, and Google Scholar) for observational studies regarding the morning serum melatonin level in RA patients from January 2000 to October 2020. The weighted mean difference (WMD) was assessed. Heterogeneity was analyzed using the Q Cochrane test and the I2 measure. To assess the relationship between covariates and effect size, we performed a meta-regression analysis. Furthermore, we used the Egger test alongside the funnel plot for the assessment of publication bias. Results: The literature search revealed 214 studies, of which 7 studies met the eligibility criteria. We did not find heterogeneity (I2 = 0.0%). This study showed a higher level of morning serum melatonin levels in RA patients in comparison with the controls (WMD = 5.85). In meta-regression analysis, none of the variables had a significant relationship with the efficacy of effect size. The funnel plot showed all the included studies were symmetrically distributed in the triangle area. Egger's test also showed an absence of publication bias. Conclusions: Melatonin levels were higher in RA patients than the controls, but due to the small sample size of included studies, the power of this meta-analysis was low.